Self-Guided Study Module for Head and Neck Radiological Anatomy - Andrew Phillips; Brian Thurber; Chad Teven; Jeremy Wortman; Alexander Soneru; Christopher Straus (Association of American Medical Colleges, 2014)
Abstract This resource is part of a five-part series of self-guided study modules exploring normal variant human radiologic anatomy. This guide examines the head and neck region and is intended for preclinical health professions students, including medical and dental students in conjunction with a gross anatomy class. A simplified, labeled atlas with serial and plain film imaging is included, although the guide is compatible with any general atlas. The guide emphasizes spatial relationships of clinically relevant structures that can be appreciated on mainstream imaging and is designed to enhance student understanding of anatomy by reinforcing multiple representations of structures. This guide, as part of the series, was examined formally in 2008 and found to have a significant increase in radiology and gross anatomy scores as compared to when students did not use the study guides. It was a paired test design to allow students to serve as their own controls.